Islamic and Conventional Bond : A Comparison Of Performance, Macroeconomic Factors and Bond Orices in Selected Four Middle East Countries - Naeem, Ibrahim (2014)
Many developed and developing economies have started to adopt the Islamic finance products into their mainstream financial system. Among the vast number of products in Islamic finance, sukuk, which is sometimes known as Islamic bond, is the most widely used instruments. Some literatures argue that sukuk and conventional bonds are same in many ways. In this paper, our main objective is to compare the performance of sukuk and conventional bond in the four selected Middles East markets; namely, United Arab Emirates (UAE), Bahrain, Qatar and Saudi Arabia. We also evaluate the price determinants of both securities across four markets and price volatility of both securities in respect to changes in the macro economic variables. Our finding shows that sukuk and conventional bond are not exactly same. The result on the performance of both securities shows that on average sukuk performs better than the conventional bonds in the selected markets. However, during the sample period, both securities failed to give a superior return than its domestic risk free rate. Analysis on price determinants shows that in UAE market, interest rates impact both securities in same direction. In addition, money supply and stock index has a significant impact on sukuk price but they do not have any impact on bond price. In Bahrain market, CPI affects the prices of both in same direction and no any other macroeconomic variable has a similar impact for both. In case of Qatar, except interest rates no any other variable has a significance impact on bond price however, variables such as GDP, money supply and stock prices has a significant influence on sukuk price. The result of Saudi market shows macroeconomic variables has no much influence on the prices of both securities. Overall, the study findings and analysis render vital implications that investors and portfolio managers in these markets should be careful in expanding their multi-dimensional portfolios to include fixed income securities such as bonds and sukuk, since the risk adjusted rate of return is lower than the domestic risk free tare. In addition, the governments and central banks authorities need to redefine their borrowing strategies and relevant policies according to changes in the market.